2007
DOI: 10.1007/s10649-007-9083-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of authenticity on sense making in word problem solving

Abstract: The study presented in this paper seeks to investigate the impact of authenticity on the students' disposition to make necessary real world considerations in their word problem solving. The aim is also to gather information about the extent to which different reasons for the students' behaviors are responsible for not providing solutions that are consistent with the 'real' situations described in the word problems. The study includes both written solutions to word problems and interview data from 161 5th grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
50

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 12 publications
(30 reference statements)
6
88
0
50
Order By: Relevance
“…He stated that it is necessary to provide environments that will allow students to become problem solvers. When the literature is examined, it is revealed that the education given to the students to be good problem solvers contributes to the development of the students [6,14,33,44,45]. [43] stated participants should be left alone with PISA questions which they will make solutions by using mathematical reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…He stated that it is necessary to provide environments that will allow students to become problem solvers. When the literature is examined, it is revealed that the education given to the students to be good problem solvers contributes to the development of the students [6,14,33,44,45]. [43] stated participants should be left alone with PISA questions which they will make solutions by using mathematical reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…Öğrencilerin yanlış cevapları incelendiğinde uygun olmayan işlem seçimi, rastgele işlem seçimi, çözümünün yarım bırakılması, işlem hatası yapılması ve problemde yer almayan sayısal verilerin kullanılması karşılaşılan yanlış tipleri olmuştur. Öğrencilerin uygun olmayan işlem seçimine ilişkin yanlışlar yaptıklarına dair kanıtlar ilgili literatürde de ifade edilmektedir (Verschaffel, De Corte ve Vierstraete, 1999, İskenderoğlu, Akbaba-Altun ve Olkun, 2004Gürcan Töre, 2007;Soylu, 2007) Xin vd., 2007Palm, 2008, Thevenot, 2010. Örneklendirmek gerekirse İskenderoğlu, Akbaba-Altun ve Olkun (2004)'nun 3., 4. ve 5. sınıf öğrencilerinin toplama ve çıkarma işlemi kullanmayı gerektiren problemlerde bu türden bir hata yaptıklarını ortaya çıkarmıştır.…”
Section: Tartişma Ve Sonuçlarunclassified
“…Authenticity represents that mathematical tasks describing the daily life situation and the actual situation outside school is consistent with a problem [11]. In order for a problem to have authenticity, the problem should deal with the context of daily life and imitate the critical parts of the actual situation as much as one can reason them [12].…”
Section: A Ill-structured Problemmentioning
confidence: 99%